Dampak Tayangan Film Kartun Terhadap Perilaku Anak Usia 5-6 Tahun - Fahruddin Fahruddin; Baik Nilawati Astini; I Nyoman Suarta; Hanny Rizkia Shavina (Indonesian Publication Center, 2022)
This research was motivated by the existence of behavioral change phenomena that have occurred in children aged 5-6 years in recent years who have been influenced by films, especially cartoons. This study aims to determine the impact of cartoon films on children's behavior. This research is a qualitative research with a case study approach. The subjects in this study were children aged 5-6 years who were in BTN West Pagutan, Mataram as many as 20 people. Data were collected through a questionnaire metho The data analysis used is descriptive qualitative analysis. The results showed that the cartoons that were often watched by children at BTN Pagutan Indah Mataram were Boboboy, Shiva, Adit and Sopo Jarwo and Upin and Ipin. Watching movies will greatly affect the behavior of children. The impact of cartoons on the behavior of children at BTN Griya Pagutan Indah Mataram, namely changes in behavior towards negative ones such as being lazy to study and preferring to watch while at home, Then behave aggressively such as fighting with his friends, often doing bicycle jumping scenes, bicycle racing, running and jumping both at home and at school. As well as often unclear emotions, and mocking each other. The positive impacts for children such as increasing children's creativity, and making it easier for children to speak Indonesian and Malaysian languages.